2021
DOI: 10.1111/jgs.17373
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist‐led interventions to improve medication adherence in older adults: A meta‐analysis

Abstract: Background/objective: As pharmacists work to ensure reimbursement for chronic disease management services on the national level, evidence of their impact on important health metrics, such as medication adherence, is needed. However, summative evidence is lacking on the effectiveness of pharmacists to improve medication adherence in older adults. The objective was to assess the effectiveness of pharmacist-led interventions on medication adherence in older adults (65+ years). Design/setting/participants: Using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 71 publications
1
17
0
Order By: Relevance
“…12 A systematic review reported that pharmacists' interventions improved patients' adherence. [26][27][28] Furthermore, a systematic review of 29 studies that used text messages to improve adherence found efficacy in interventions that used motivational messages. 29 Therefore, for Asian patients, more aggressive interventions are needed by pharmacists for preoperative discontinuation of medications.…”
Section: Discussionmentioning
confidence: 99%
“…12 A systematic review reported that pharmacists' interventions improved patients' adherence. [26][27][28] Furthermore, a systematic review of 29 studies that used text messages to improve adherence found efficacy in interventions that used motivational messages. 29 Therefore, for Asian patients, more aggressive interventions are needed by pharmacists for preoperative discontinuation of medications.…”
Section: Discussionmentioning
confidence: 99%
“…At present, few studies have evaluated the effect of medication reconciliation on patient adherence across countries; those that have done so were rated as having a low certainty of the evidence [ 31 ]. A previous meta-analysis showed that pharmacist-led interventions, especially patient education, were found to have effect on improving medication adherence in older adults [ 32 ]. Thus, the improvement we observed in patient adherence may be attributable to patient counselling and education contained in the medication reconciliation intervention.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown to lower or avert the increase of disease-related medical costs. [1][2][3][4][5][6][7] Nonetheless, and particularly as regards cardiovascular disease, adherence to medications remains a major challenge, with nonadherence leading to poor clinical outcomes, rehospitalizations, subsequent myocardial infarction, and increased mortality. 8 Contributing factors to sub-optimal adherence include patient-related and treatment-related factors.…”
Section: Introductionmentioning
confidence: 99%
“…6,19 To address this persistent challenge of nonadherence, the literature reports on several pharmacist-led interventions that have shown a positive impact on patients' adherence to medication and clinical outcomes. 4,5,20,21 For instance, enrollment in a medication adherence program in community pharmacies in New Zealand improved adherence, with individuals in the intervention group having 2.99 (95% CI: 2.79-3.20) greater odds of being adherent 12 months after the start of the study. 20 Elsewhere, patients were telephoned by pharmacists monthly to assess changes in adherence to medication for diabetes, hypertension, or hyperlipidemia therapies over 6 months.…”
Section: Introductionmentioning
confidence: 99%